Bahan Ajar: Tujuan, Jenis, Dan Prinsip Pengembangan - Indah Dina Pratiwi (Jurnal Penelitian dan Ilmu-Ilmu Keislaman, 2021)
Learning materials or teaching materials are a set of subject matter that can help achievecurriculum goals, which are arranged systematically and intact so as to create a pleasant learningenvironment, make it easier for students to learn, and teachers teach. The types of teachingmaterials are distinguished based on their form, working method, nature, and based on theirsubstance or content. Examined from its form, how it works, and its nature, teaching materials areinterpreted from the perspective of how they are presented. Meanwhile, based on the substance,teaching materials are described as concepts, facts, principles, and procedures. The developmentof teaching materials must comply with the principle of relevance, the principle of constancy orconsistency, and the principle of adequacy